Bezpieczeństwo sieci i usług łączności elektronicznej w prawie Unii Europejskiej oraz w prawie polskim - Rogalski, Maciej, 1966- (Uczelnia Łazarskiego, 2024)
"The book is devoted to the security of electronic communications networks and services. This issue is analyzed primarily from the regulatory aspect. The provisions of both European Union and Polish law are discussed. National regulations in the field of cybersecurity are based on EU regulations. Therefore, the work presents the provisions of the directive of December 14, 2022 on measures for a high common level of cybersecurity in the territory of the Union (NIS 2 directive) and the directive of December 11, 2018 establishing the European Electronic Communications Code, as well as the regulation on ENISA (European Union Agency for Cybersecurity) and cybersecurity certification in the field of information and communication technologies. Finally, the provisions of the Cybersecurity of 5G networks EU Toolbox of risk mitigating measures (5G Toolbox) are presented, which does not have the character of EU regulations, but is important in the field of cybersecurity. In the area of national regulations, the provisions of the Telecommunications Law and the Regulation of the Minister of Digital Affairs of June 22, 2020 on minimum technical and organizational measures and methods that telecommunications entrepreneurs are obliged to use to ensure the security or integrity of networks or services are discussed. Some programmatic documents are also presented, in particular the Polish Cybersecurity Strategy. A significant part of the monograph is devoted to the proposed legal regulations, in particular the proposed Electronic Communications Act and the amendment to the Act on the national cybersecurity system, including the requirements for suppliers of telecommunications equipment necessary for the construction of 5G infrastructure, resulting from the 5G Toolbox."--